Strategy For Localization Of Foreign Human Resources In Pt Krakatau Posco - Nam Gihun (Cakrawala Repositori IMWI, 2024)
The purpose of this paper is to examines how strategy for localization of foreign human resource in term of Korean technical assistance and Indonesia workers. We analyse some characteristic of both of countries internal and external factors, offering win - win solution. Using qualitative and quantitative dataset from internal data, measuring by Likert scale 1 to 5, interview and survey did to get clear conclusion. Localization is good in some conditions, but for long term it will be made problems and company must support local employees to develop their skill, knowledge with policy and role in company.